ECONOMIC EFFICIENCY ANALYSIS OF THE APPLICATION OF ELECTRIC TRANSPORT VEHICLES – CASE STUDY - Hartványi, Tamás; Hencz, Csaba I. (Advanced Logistic Systems - Theory and Practice, 2016)
In the current logistics common the small amount and short-range transport. The increasing complexity, decreasing batch sizes, shortened product life cycles and the continuously declining stock sizes lead to regular scheduled deliveries appreciation in the value. The enterprises are almost exclusively internal combustion engine trucks used for these deliveries. In turn within the factories and warehouses used generally electric material handling machines. In our study we explore those areas of application where the use of electric or hybrid vehicles may have economic benefits, instead of using internal combustion vehicles. As an example we present the potential costs of a transport-logistics system.